Magnetic storm observations from the Prague-Clementinum observatory on 1846-09-22 - Pavel Hejda; Miloš Revallo; Fridrich Valach (PANGAEA, 2021)
Data of magnetic storms recorded at the Prague-Clementinum observatory in 1839-1849 are presented. The data were obtained by digitising and processing the original old records published in the yearbooks of this historical observatory. The data set contains variation of declination [min] and horizontal magnetic field [nT] of 73 magnetic storms with the magnitudes being of at least a moderate level completed with the baseline of declination [deg] and baseline of horizontal megnetic field [nT]. All time data were transformed into UT, based on the longitude of the Göttingen observatory, which was 9.950°. The time shift is thus 39 extquotesingle48 extquotesingle extquotesingle. The date in the file name indicates the start day of the storm.
In: Hejda, P et al. (2021): Data of magnetic storms and term-day observations from the Prague-Clementinum observatory (1839-1849) [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.936921